2010
DOI: 10.1016/j.bcp.2009.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib and erlotinib are potent reversal agents for MRP7 (ABCC10)-mediated multidrug resistance

Abstract: In recent years, a number of TKIs (tyrosine kinase inhibitors) targeting epidermal growth factor receptor (EGFR) family have been synthesized and some have been approved for clinical treatment of cancer by the FDA. We recently reported a new pharmacological action of the 4-anilinoquinazoline derived EGFR TKIs, such as lapatinib (Tykerb®) and erlotinib (Tarceva®), which significantly affect the drug resistance patterns in cells expressing the multidrug resistance (MDR) phenotype. Previously, we showed that lapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 37 publications
5
90
0
Order By: Relevance
“…Our previous findings showed lapatinib could inhibit the function of ABCB1, ABCG2 and MRP10 (26,27). To demonstrate the interaction of lapatinib and other MDR proteins, the cell lines C-A120, HEK293/ MRP2 and NIH3T3/MRP4-2 as well as SW1573/ 2R120 were used in our research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous findings showed lapatinib could inhibit the function of ABCB1, ABCG2 and MRP10 (26,27). To demonstrate the interaction of lapatinib and other MDR proteins, the cell lines C-A120, HEK293/ MRP2 and NIH3T3/MRP4-2 as well as SW1573/ 2R120 were used in our research.…”
Section: Discussionmentioning
confidence: 99%
“…Lapatinib is an orally active dual TKI that has been used in combination with capecitabine or letrozole for the treatments of patients with advanced breast cancer (25). We previously reported that lapatinib inhibited the function of ABCB1, ABCG2 and MRP10 (26,27). In this study, we explored the effect of lapatinib on the efficacy of conventional chemotherapeutic agents in MRP1-, MRP2-, MRP4-and LRP-overexpressing cancer cells in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of P-glycoprotein-mediated drug resistance by erlotinib appears to be substrate dependent (Shi et al, 2007;Noguchi et al, 2009). In addition, Kuang et al reported that erlotinib potently reverses MRP7-mediated multidrug resistance (Kuang et al, 2010). Thomas et al (2009) reported population pharmacokinetics in erlotinib-treated patients with head and neck squamous cell carcinoma.…”
Section: Erlotinibmentioning
confidence: 99%
“…ABCG2-transfected cells exhibited lower intracellular accumulation of erlotinib than cells lacking ABCG2, indicating that erlotinib is a substrate of Gnoth et al, 2010), K562 cells (Haouala et al, 2010), LLC-PK1 cells (Hu et al, 2009;Gnoth et al, 2010), MDCKII cells (Lagas et al, 2010) Abcb1a/1b(-/-) mice (Hu et al, 2009;Gnoth et al, 2010), Abcb1a/1b(-/-) Abcg2(-/-) mice (Lagas et al, 2010;Asakawa et al, 2011) MRP2 (ABCC2) LLC-PK1 cells (Shibayama et al, 2011) BCRP (ABCG2) MDCKII cells (Lagas et al, 2010;Agarwal et al, 2011) Abcg2(-/-) mice (Lagas et al, 2010;Agarwal et al, 2011), Abcb1a/1b(-/-) Abcg2(-/-) mice (Lagas et al, 2010;Agarwal et al, 2011;Asakawa et al, 2011) Sunitinib P-glycoprotein (ABCB1) K562 cells (Haouala et al, 2010), LLC-PK1 cells (Hu et al, 2009), MDCKII cells Abcb1a/1b(-/-) mice (Hu et al, 2009;Tang et al, 2011), (Minematsu and Giacomini, 2011) MATE2-K (SLC47A2) Metformin (IC50 = 3.45 mM) HEK293 cells (Minematsu and Giacomini, 2011) P-glycoprotein (ABCB1) Vincristine (IC50 = 2 mM) K562 cells (Noguchi et al, 2009) MRP7 (ABCC10) Paclitaxel HEK293 cells (Kuang et al, 2010) BCRP (ABCG2) E 217bG, methotrexate, mitoxantrone HEK293 (Shi et al, 2007), K562 cells (Noguchi et al, 2009) Gefitinib OCT1 (SLC22A1) MPP + HEK293 cells (Galetti et al, 2010) OCT2 (SLC22A2) MPP + HEK293 cells (Galetti et al, 2010) MATE2-K (SLC47A2) Metformin (IC50 = 0.194 mM) HEK293 cells (Minematsu and Giacomini, 2011) P-glycoprotein (ABCB1) Calcein-AM, docetaxel, doxorubicin, paclitaxel, rhodamine-123, topotecan CL1 cells (Yang et al, 2005), LL...…”
Section: Erlotinibmentioning
confidence: 99%
See 1 more Smart Citation